Pengaruh Penyuluhan Kesehatan Lingkungan Terhadap Pencegahan Penyakit Demam Berdarah Di Kelurahan Paal Dua Kecamatan Paal Dua Kota Manado - Stefanus Timah (JURNAL ILMIAH KESEHATAN MANADO, 2025)
The infectious disease caused by viruses from Arbovirosis groups A and B which is problematic in Indonesia is known as Dengue Hemorrhagic Fever (DHF) which is an endemic disease and causes health problems, not only in Indonesia but also in tropical and subtropical countries around the world. The aim of the research is to determine the relationship between community behavior and the incidence of dengue fever in the Paal Dua sub-district area, Manado City. The target of this service is the entire community in Kleak Village, Paa Dua District, Manado City. From the results of community service, it is known that there is a significant relationship between knowledge and the incidence of dengue fever, there is a significant relationship between attitudes and the incidence of dengue fever.